Rhizodegradation of Pyrene by a Non-pathogenic Klebsiella pneumoniae Isolate Applied With Tagetes erecta L. and Changes in the Rhizobacterial Community - Rajkumari, Jina; Choudhury, Yashmin; Bhattacharjee, Kasturi; Pandey, Piyush (Frontiers in Microbiology, 2021)
The non-clinical Klebsiella pneumoniae variants, isolated from different environments, are now well acknowledged for their role in plant growth promotion and biodegradation of pollutants. In present study, a non-clinical environmental isolate K. pneumoniae AWD5 is being described for rhizoremediation of pyrene, applied through rhizosphere of an ornamental plant, Tagetes erecta L. The non-pathogenic nature of AWD5 was established using in-vivo mice model experiment, where AWD5 was unable to cause lung infection in tested mice. Degradation of pyrene, in the presence of succinate as co-substrate was observed to be 87.5% by AWD5, after 21 days of incubation in minimal (BushnellHass) medium in vitro conditions. Consequently, the bacterial inoculation through rhizosphere of T. erecta L. plants resulted 68.61% degradation of pyrene, which was significantly higher than control soil. Inoculation of AWD5 also improved plant growth and exhibited increase in root length (14.64%), dry root weight (80.56%), shoot length (3.26%) and dry shoot weight (45.35%) after 60 days of incubation. T. erecta L., an ornamental plant, was also found to be suitable for the purpose of bioremediation of pyrene. The effect of AWD5 application, and rhizoremediation process, on rhizosphere bacterial diversity and community structure has been studied using the metagenomic analysis of 16S (V3-V4) region of rRNA. 37 bacterial phyla constituted the core microbiome, which was dominated by Proteobacteria followed by Actinobacteria, Actinobacteria, and Planctomycetes for all the treatments. AWD5 inoculation enhanced the relative abundance of Firmicutes and Acidobacteria as compared with other treatments. Genus Kaistobacter, Verrucomicrobia was found to be abundant indigenous population in pyrene spiked soils. Bacterial richness and diversity were analyzed using Shannon-Wiener (H) index. Lower diversity index was observed in pyrene spiked soils. Canonical correspondence analysis (CCA) showed possible linkage with plant growth attributes and available nitrogen content that influences diversity and abundance of bacterial community.